A proposed training program to develop some concepts among kindergarten children using games (Journal of the College of Basic Education, 2022)
Our Iraqi society has witnessed, and still is, abnormal conditions that affected and reflected on kindergartens. Today, kindergartens have become a place to shelter the child during the absence of the mother at work. Concepts There is no interest in the programs that achieve the goals of Riyadh, as the current experiences in our kindergarten are limited to memorization and indoctrination only. The upbringing of the child from birth, especially in the early years, has an impact on all the roles of his life after that. .